2019
DOI: 10.3390/w11040705
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Severe Drought Area Based on Random Forest: Using Satellite Image and Topography Data

Abstract: The uncertainty of drought forecasting based on past meteorological data is increasing because of climate change. However, agricultural droughts, associated with food resources and determined by soil moisture, must be predicted several months ahead for timely resource allocation. Accordingly, we designed a severe drought area prediction (SDAP) model for short-term drought without meteorological data. The predictions of our proposed SDAP model indicate a forecast of serious drought areas assuming non-rainfall, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 47 publications
0
31
0
Order By: Relevance
“…This study has the framework of two linked models, as shown in Figure 2, which is a structure that simulates policy by SD model based on the result of SDAP model [13]. The SDAP model ( Figure 3) predicts the spatial distribution pattern of soil moisture after non-rainfall period using drought function trained by random forest (RF) algorithm [13]. The SD model (Figure 4) estimates the amount of water available to the provincial government by simulating the price increase policy for the drought-tolerant areas predicted in the previous process.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…This study has the framework of two linked models, as shown in Figure 2, which is a structure that simulates policy by SD model based on the result of SDAP model [13]. The SDAP model ( Figure 3) predicts the spatial distribution pattern of soil moisture after non-rainfall period using drought function trained by random forest (RF) algorithm [13]. The SD model (Figure 4) estimates the amount of water available to the provincial government by simulating the price increase policy for the drought-tolerant areas predicted in the previous process.…”
Section: Methodsmentioning
confidence: 99%
“…Agricultural drought was trained and predicted by the following concept [13]. The soil moisture after non-rainfall periods remains different depending on the condition of the present land surface [20].…”
Section: Sdap Model: Prediction Drought Spatial Distributionmentioning
confidence: 99%
See 2 more Smart Citations
“…where R, σ P , and σ O are, respectively, correlation coefficient between TRMM and observational precipitation, standard deviation of TRMM precipitation data, and standard deviation of observational precipitation data. The NRMSE represents the mean square error dimensionless, and it is calculated by Equation (5) [21]:…”
Section: Statistical Indicatorsmentioning
confidence: 99%